2012
DOI: 10.1128/aac.06232-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Comparison of Two Piperaquine-Containing Artemisinin Combination Therapies in Papua New Guinean Children with Uncomplicated Malaria

Abstract: Pharmacokinetic differences between piperaquine (PQ) base and PQ tetraphosphate were investigated in 34 Papua New Guinean children aged 5 to 10 years treated for uncomplicated malaria with artemisinin-PQ (ART-PQ) base or dihydroartemisinin-PQ (DHA-PQ) tetraphosphate. Twelve children received ART-PQ base (two daily doses of 3 mg of ART and 18 mg of PQ base as granules/kg of body weight) as recommended by the manufacturer, with regular clinical assessment and blood sampling over 56 days. PQ concentrations in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
(108 reference statements)
4
20
1
Order By: Relevance
“…As found previously (39), there was significant variability in the absorption phase of PQ. Therefore, a transit compartment model, previously shown to be effective in characterizing the absorption phase of PQ (39), was also tested.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…As found previously (39), there was significant variability in the absorption phase of PQ. Therefore, a transit compartment model, previously shown to be effective in characterizing the absorption phase of PQ (39), was also tested.…”
Section: Methodssupporting
confidence: 58%
“…As found previously (39), there was significant variability in the absorption phase of PQ. Therefore, a transit compartment model, previously shown to be effective in characterizing the absorption phase of PQ (39), was also tested. In this model, the dose passes through a series of transit compartments before entering the absorption compartment, in order to model the delay often associated with drug absorption.…”
Section: Methodssupporting
confidence: 58%
“…The piperaquine data appear to be conflicting; however, there were several clinical differences between the two populations and no conclusive explanation for the findings (56,57). Two recent reports of piperaquine pharmacokinetics showed lower CL/F values, suggesting that the rule of exponents may be applicable to piperaquine, but as noted in Table 4, these data could not be included in the present study due to the use of pooled results from different partner drugs (12) and use of capillary blood analysis to determine the pharmacokinetic parameters (13). Quinine predictions are problematic, due to the difference in CL (and V z ) between healthy subjects and patients with malaria, and the reported lower CL in children than adults (Table 3).…”
Section: Discussioncontrasting
confidence: 42%
“…There is no significant difference in piperaquine clearance when piperaquine is administered alone or in combination with dihydroartemisinin (148). One recent study reported a CL/F of 0.57 liter/h/kg; however, the data were pooled from a previous study of piperaquine-dihydroartemisinin (57) and an investigation of piperaquine-artemisinin (12). A report of a piperaquine CL/F of 0.42 liter/h/kg from capillary blood samples could not be compared directly to investigations using venous plasma samples for determination of piperaquine pharmacokinetic parameters (13).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation